Purification and characterization of bacteriocin produced by a strain of Lacticaseibacillus rhamnosus ZFM216 - Wu, Danli; Dai, Mengdi; Shi, Yongqing; Zhou, Qingqing; Li, Ping; Gu, Qing (Frontiers in Microbiology, 2022)
The recent surge in demand for natural preservatives has ushered in a new era of research into novel bacteriocins capable of effectively combating food-borne infections. In this study, the bacteriocin from Lacticaseibacillus rhamnosus ZFM216 (L. rhamnosus ZFM216), which has a molecular mass of 11851.9 Da, was purified using macroporous resin, gel chromatography, and reversed-phase high performance liquid chromatography (RP-HPLC). This bacteriocin could inhibit both gram-positive and gram-negative bacteria. The minimal inhibitory concentration (MIC) for Staphylococcus aureus D48 (S. aureus D48) was 1.75 μM. Bacteriocin ZFM216 was heat stable and showed pH stability under weakly acidic conditions. It was sensitive to pepsin, proteinase K and trypsin but not to papain. Electron microscopy results showed that when treated with bacteriocin ZFM216, S. aureus D48 was severely deformed, the cell structure was obviously changed, and the intracellular electrolyte leaked to the outside of the cell. Bacteriocin ZFM216 caused the ATP level of the indicator to decrease, the conductivity to sharply increase, and the transmembrane potential difference (ΔΨ) to instantaneously decrease. This research formed the basis for further development and utilization of bacteriocin ZFM216 which has potential in the food industry.